Product ion distributions for the reactions of NO+ with some physiologically significant volatile organosulfur and organoselenium compounds obtained using a selective reagent ionization time‐of‐flight mass spectrometer. (18th June 2014) - Mochalski, Paweł; Unterkofler, Karl; Španěl, Patrik; Smith, David; Amann, Anton
<x xml:space="preserve">Abstract</x> RATIONALE The reactions of NO+ with volatile organic compounds (VOCs) in Selective Reagent Ionization Time‐of‐Flight Mass Spectrometry (SRI‐TOF‐MS) reactors are relatively poorly known, inhibiting their use for trace gas analysis. The rationale for this product ion distribution study was to identify the major product ions of the reactions of NO+ ions with 13 organosulfur compounds and 2 organoselenium compounds in an SRI‐TOF‐MS instrument and thus to prepare the way for their analysis in exhaled breath, in skin emanations and in the headspace of urine, blood and cell and bacterial cultures. METHODS Product ion distributions have been investigated by a SRI‐TOF‐MS instrument at an E/N in the drift tube reactor of 130 Td for both dry air and humid air (4.9% absolute humidity) used as the matrix gas. The investigated species were five monosulfides (dimethyl sulfide, ethyl methyl sulfide, methyl propyl sulfide, allyl methyl sulfide and methyl 5‐methyl‐2‐furyl sulfide), dimethyl disulfide, dimethyl trisulfide, thiophene, 2‐methylthiophene, 3‐methylthiophene, methanethiol, allyl isothiocyanate, dimethyl sulfoxide, and two selenium compounds – dimethyl selenide and dimethyl diselenide. RESULTS Charge transfer was seen to be the dominant reaction mechanism in all reactions under study forming the M+ cations. For methanethiol and allyl isothiocyanate significant fractions were also observed of the stable adduct ions NO+M, formed by ion‐molecule association, and [M–H]+ ions, formed by hydride ion transfer. Several other minor product channels are seen for most reactions indicating that the nascent excited intermediate (NOM)+* adduct ions partially fragment along other channels, most commonly by the elimination of neutral CH3, CH4 and/or C2H4 species that are probably bound to an NO molecule. Humidity had little effect on the product ion distributions. CONCLUSIONS The findings of this study are of particular importance for data interpretation in studies of volatile organosulfur and volatile organoselenium compounds employing SRI‐TOF‐MS in the NO+ mode. © 2014 The Authors. Rapid Communications in Mass Spectrometry published by John Wiley & Sons Ltd.